Change in serum KL-6 level from baseline is useful for predicting life-threatening EGFR-TKIs induced interstitial lung disease - Kawase, Shigeo (BioMed Central, 2011)
BACKGROUND: A high incidence of interstitial lung disease (ILD) has been reported in patients with advanced non-small cell lung cancer (NSCLC) treated with epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs), particularly in Japanese populations. A previous report from our laboratory demonstrated that KL-6 was a useful serum biomarker to assess the severity of drug-induced pneumonitis. Based on these observations, this study was conducted to evaluate the risk factors of EGFR-TKIs induced ILD and the usefulness of monitoring serum KL-6 levels in patients who developed EGFR-TKIs induced ILD in a large multi-institutional setting. METHODS: We retrospectively reviewed clinical records and radiographies of 341 patients with advanced NSCLCs who were treated with EGFR-TKIs, and analyzed risk factors for the development of EGFR-TKIs induced ILD. Changes of circulating levels of KL-6 were also evaluated in the patients who developed EGFR-TKIs induced ILD. RESULTS: Among the 341 patients included in this study, 20 (5.9%) developed EGFR-TKIs induced ILD, and 9 (2.6%) died from ILD. Univariate analyses revealed that only preexisting pulmonary fibrosis was a significant risk factor for the development of EGFR-TKIs induced ILD (p = 0.003). Absolute levels of circulating KL-6 at neither baseline nor the onset of ILD could discriminate between life-threatening and non-life threatening EGFR-TKIs induced ILDs. However, we found that the ratios of serum KL-6 levels just after the onset of EGFR-TKIs induced ILD to those at baseline could quite precisely distinguish survivors from non-survivors (p = 0.006) as well as acute interstitial pneumonia (AIP) pattern from non-AIP pattern (p = 0.005). CONCLUSIONS: The results of this study strongly support the potential of KL-6 as a diagnostic biomarker for life-threatening EGFR-TKIs induced ILD. Monitoring of KL-6 is also useful to evaluate the progression and severity of EGFR-TKIs induced ILD.